PREPAREDNESS OF MIDDLE AGED COUPLES FOR OLD AGE - SANGEETA BHATT*; GAYTRI TIWARI (The Journal of Research ANGRAU, 2023)
The study was undertaken in the year 2018 to assess the preparation level of middle aged couples for old ageliving in the Udaipur City. The sample for the study consisted of 100 single earner middle aged couples belonging to the age range of 50 – 60 years. A general information proforma was used to collect the background information of the subjects. ‘Preparation for Old Age Scale’ was developed to assess the level of preparation. The data obtained were analysed and assessed using percentage distribution, mean scores and z-test. Major findings of the study indicated that majority (59%) of the couples had moderate level of preparation for old age with men scoring higher than women, respectively. Couples were best prepared in the mental dimension of preparation area and had lowest preparation in socio-emotional dimension with mean scores of 34.085 and 29.515, respectively.